2022
DOI: 10.3390/cells11030427
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Fibrosis in Human Atrial Tissue Is Not the Hallmark Driving AF

Abstract: Background: The current paradigm is that fibrosis promotes electrophysiological disorders and drives atrial fibrillation (AF). In this current study, we investigated the relation between the degree of fibrosis in human atrial tissue samples of controls and patients in various stages of AF and the degree of electrophysiological abnormalities. Methods: The degree of fibrosis was measured in the atrial tissue and serum of patients in various stages of AF and the controls. Hereto, picrosirius and H&E staining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…In goats, after 6 months of rapid atrial pacing-induced AF, atrial endomysial fibrosis increases, whereas quantities of total ECM remain constant (9), a combination of findings resembling well the findings of the current study. Recently, a study of cardiac surgery patients reported no association between electrophysiological parameters and histological fibrosis markers (59). Electrophysiological measurements, however, were performed at low rates and a distinction between total and endomysial fibrosis was only made in a small percentage of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In goats, after 6 months of rapid atrial pacing-induced AF, atrial endomysial fibrosis increases, whereas quantities of total ECM remain constant (9), a combination of findings resembling well the findings of the current study. Recently, a study of cardiac surgery patients reported no association between electrophysiological parameters and histological fibrosis markers (59). Electrophysiological measurements, however, were performed at low rates and a distinction between total and endomysial fibrosis was only made in a small percentage of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study of cardiac surgery patients reported no association between electrophysiological parameters and histological fibrosis markers (59). Electrophysiological measurements, however, were performed at low rates and a distinction between total and endomysial fibrosis was only made in a small percentage of patients.…”
Section: Af and Structural Remodelingmentioning
confidence: 99%
“…Recently, Ramos and colleagues could similarly demonstrate that in patients with AF the absolute degree of fibrosis is not the key driver for AF. 19 Furthermore, they could show that the heterogeneous distribution of fibrosis within the right atrial appendage does not correlate with altered electrical conduction properties. 19 As interstitial fibrosis has been demonstrated to establish local conduction heterogeneities leading to AF, [2][3][4]14 we hypothesized that not only localized but also cross-regional fibrosis heterogeneity contributes to AF.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrosis is a common feature in AF patients, yet how and if atrial fibrosis is involved in AF generation is poorly understood [91]. Ramos et al reported recently that the amount of atrial fibrosis is not different in patients with various stages of AF and controls [92]. It is atrial structural remodelling rather than atrial fibrosis that can be causal for AF [92].…”
Section: Pathophysiology Of Atrial Fibrillationmentioning
confidence: 99%
“…Ramos et al reported recently that the amount of atrial fibrosis is not different in patients with various stages of AF and controls [92]. It is atrial structural remodelling rather than atrial fibrosis that can be causal for AF [92]. Interestingly, mild and moderate atrial fibrosis has been reported to be associated with an increase of AF burden and advanced atrial fibrosis (encountered in patients with severe HF) is associated with a reduction of AF burden [93,94].…”
Section: Pathophysiology Of Atrial Fibrillationmentioning
confidence: 99%